Tensile membrane action of reinforced concrete slabs - Hansidi, Dhany. (2010)
Tensile Membrane Action (TMA) is a self-equilibrating mechanism of laterally unrestrained reinforced concrete slabs comprising a tensile net in the central region surrounded by a peripheral compressive ring of concrete. This phenomenon happens in reinforced concrete slabs with the presence of vertical support continuously along perimeter edges after the failure of flexural mechanism at very large deformations. TMA is not a common phenomenon and only occurs in severe conditions such as column loss condition due to explosion. The study of TMA has become more essential nowadays as this mechanism is able to provide alternate load path in mitigating progressive collapse. The potential for progressive collapse of reinforced concrete building structures can be evaluated by means of column loss scenarios. Under a column loss scenario, the associated beam-slab structure is subjected to uniform gravity loading amplified by both doubling of span and dynamic factor larger than 1. In such a situation, TMA is a vital alternative load path for flexural mechanism which fails to sustain the amplified gravity load. The loss of penultimate internal column is the most critical scenario as it leaves the respective beam-slab structure with horizontally unrestrained boundary condition. Research works have been conducted extensively on investigating the development of TMA, but most of them focus on either laterally restrained or simply supported reinforced concrete slabs. Through this research, the author wishes to study TMA in laterally unrestrained reinforced concrete beam-slab structures subjected to penultimate internal column loss.